Autorski idiolekt pisarski Józefa Piłsudskiego - Dubisz, Stanisław (Idiolekty, 2025)
This article investigates the ten-volume edition of Józef Piłsudski’s works "Pisma zbiorowe. Wydanie prac dotychczas drukiem ogłoszonych" ["Collected Writings: A Compilation of Previously Published Works", Warsaw 1937–1938]. Its primary goal is to identify linguistic features that exhibit idiolectal characteristics – those that Piłsudski employed with particular preference or that distinguish his texts from contemporaneous writings. While these texts do not offer a verbatim account of Piłsudski’s individual spoken language due to the editorial nature of the collection, they can nonetheless be interpreted as a representation of his autolekt, or his distinctive authorial writing style. The study identifies 48 linguistic features, divided into three categories: general features of the Polish language, Northern Borderlands regionalisms, and authorial idiolectisms. The findings suggest that Józef Piłsudski’s autolekt exemplifies standard Polish, with regionalisms and idiolectisms serving as ornamental and supplementary elements in his texts.